2019
DOI: 10.3892/ol.2019.10722
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic roles of MAGE family�members in breast cancer based on KM‑Plotter Data

Abstract: Breast cancer is the second leading cause of cancer-associated mortality among women worldwide, and the prevalence and mortality rates associated with this disease are high in Western countries. The melanoma-associated antigen (MAGE) family proteins are well-known tumor-specific antigens; this family includes >60 proteins that serve an important part in cell cycle withdrawal, neuronal differentiation and apoptosis. The aim of the present study was to identify a biomarker within the MAGE family that is specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 49 publications
(48 reference statements)
1
24
0
Order By: Relevance
“…2c,d). MAGEH1 expression had less in uence on ovarian cancer and as reported [19], high MAGEH1 expression had an association with inferior RFS in breast cancer (Fig. 2h).…”
Section: Mageh1 Expression-prognosis Associationsupporting
confidence: 69%
See 1 more Smart Citation
“…2c,d). MAGEH1 expression had less in uence on ovarian cancer and as reported [19], high MAGEH1 expression had an association with inferior RFS in breast cancer (Fig. 2h).…”
Section: Mageh1 Expression-prognosis Associationsupporting
confidence: 69%
“…Ojima and his colleagues highlighted the role of negativeexpressed MAGEH1 in the effectiveness of Gemcitabine therapy for biliary cancer [17]. Moreover, previous work stated that low expression of MAGEH1 could promote the progression of hepatocellular carcinoma (LISC) and serve as a marker for prognosis in its patients [18], while over-expressed MAGEH1 predicted an adverse prognosis in breast cancer [19]. These ndings suggest that MAGEH1 has an underlying impact on the progression of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Their reactivation during neoplastic transformation may play an important role in immunosurveillance, as MAGE proteins are antigens expressed by several malignancies [ 111 ]. Although their expression is not yet well investigated in PDAC, a recent study showed that high expression levels of MAGEB4 mRNA in breast cancer patients correlate with an improved relapse-free survival, regardless of breast cancer subtype [ 112 ]. GLI3 and MEGF8 belong to the well-known hedgehog (HH) signaling cascade, frequently altered in PDAC [ 113 ].…”
Section: Genetic and Molecular Features Of Pdac Variantsmentioning
confidence: 99%
“…For preliminary validation of the expression of the hub genes in our model, we referred to the immunohistochemical results from Human Protein Atlas [38] (https://www.proteinatlas.org). Also, the Kaplan-Meier plotter [39](https://kmplot.com) was used for overall survival analysis.…”
Section: Online Con Rmation Of the Six Hub Genesmentioning
confidence: 99%